IMPACT OF ENVIRONMENT ACCOUNTING DISCLOSURES ON PROFITABILITY AND FIRM VALUE OF PETROCHEMICAL INDUSTRY IN THE PHILIPPINES - Cruz Merrie Anne A; Dela Peña Cheska; Mahinay Ronniell; Santiago Edward James (International Interdisciplinary Conference on Sustainable Development Goals, 2022)
Environmental Accounting is an emerging subject of interest globally as a link between accounting and environmental management. This study aims to examine the impact of Environmental Accounting Disclosure (EAD) on the firm’s profitability and firm value. The object used in this study was the thirty (30) publicly-listed chemical, mining and oil companies under the Petrochemical Industry in the Philippines which are considered as pollutant contributors. Causal-explanatory research was utilized. Financial and environmental data from years covering 2015-2019 were gathered from secondary sources specifically, Annual Reports and Annual Corporate Governance Reports of these companies. Environmental Accounting Disclosure (EAD) was measured using EAD Index. Profitability was measured through the use of Return on Assets, Return on Equity, Net Profit Margin and Debt to Equity Ratio whereas, firm value was measured by Tobin’s Q. Furthermore, firm’s size and age were used as moderating variables. This study concluded that it has no significant effect on either the profitability and firm value. Therefore, whether environmental information was disclosed, it would not affect the independent variables. However, when moderated by firm size, it gives a significant effect to the profitability. This implies that as the firm increases in size, EAD significantly impacts the profitability.